Integrasi Kearifan Lokal dalam Pembelajaran Sejarah: Tinjauan atas Kurikulum Merdeka - Siregar, Muhammad Andre Syahbana; Suboh, Amerruddin Shah (Education & Learning, 2025)
This article aims to examine the integration of local wisdom in history education, focusing on the review of the implementation of the "Kurikulum Merdeka" (Independent Curriculum) in Islamic schools (madrasahs). The "Kurikulum Merdeka" is considered a solution that plays a foundational role in incorporating local history as an inseparable component. The approach adopted by the "Kurikulum Merdeka" specifically emphasizes the formation of individual character, where students are encouraged to understand and apply the values of Pancasila. The research methodology applied is a descriptive qualitative research method using a literature review. Data were collected from various literature sources such as books, articles, or research findings related to the educational curriculum in Indonesia, including the "Kurikulum Merdeka." The data used in this study are secondary, consisting of a curriculum review of history subjects at the high school level (SMA/MA/Equivalent). The "Kurikulum Merdeka" serves as a solution for integrating local history as an inseparable element, with a focus on shaping students' characters through the values of Pancasila and local wisdom. Despite facing global dynamics, the "Kurikulum Merdeka" still recognizes and prioritizes local wisdom as a fundamental foundation. The implementation of local wisdom aims to preserve cultural diversity without losing values while remaining open to the positive influences of foreign cultures. In line with this, history education integrated with local culture plays a crucial role in preserving wisdom, fostering nationalism, and developing a profound understanding of the nation's history. Curriculum integration, involving student participation and an interdisciplinary approach, is expected to create a younger generation that understands and takes pride in their national identity. Historical awareness, especially through the "Kurikulum Merdeka," becomes a crucial foundation in the effort to build the nation's character, with the hope that the nation will learn from history and grow into a culturally rich and civilized society in the future